Pengaruh e-servqual Terhadap Niat Pembelian Pelanggan Online's - Mahjudin, * (Program Doktor Ilmu Ekonomi, 2013)
In the recent days, internet has become the best and popular media for consumer’s shopping channel. But there are differences on the shopping behavior between rural and suburban people which is beneficial to be discussed. This research aimed to compare the culture effect of any online consumer’s shopping between Urban Buyer dan Rural Buyer. 120 questionaires were distributed amnong Rural Buyer respondents. Statistical Analysys software of SPSS 17.0 and AMOS 6.0 were used to analyze the effect between two countries on e-service quality, satisfaction, trust, dan buying intention. The results of the research showed that the research model proposed is acceptable on certain level and it showed that the research theoretical model supported the description that online shopping situation will be influenced by trust and satisfaction. But, dealing with culture in online shopping situation and the relationship of e-service quality, there are significant differences on the trust and satisfaction between two segments. This created cultural difference which influenced the process of online shopping. The result of the research will be available for them who have interests on developing transnational e-retailer as references, and academical risearch on cross cultural comparative analysis/ Keyword: Cukture, Shopping Behavior, Trust, Satisfaction.